International NGO Centralization and Leader-Perceived Effectiveness. (February 2020) - Tran, Long
Although international nongovernmental organizations (INGOs) rely on their governance structures to pursue crucial missions across national borders, the extant literature is lacking theoretical insights and empirical evidence that explain the influence of such structures on INGO effectiveness. Using organizational and psychological theories, socially constructed effectiveness measurement, and data on 152 U.S.-based INGOs, this study explores how centralization, a fundamental structural characteristic, relates to an INGO's effectiveness as perceived by its own leader versus by leaders of other INGOs. Quantitative and qualitative findings suggest that centralized, unitary INGOs tend to have stronger internally perceived effectiveness but weaker externally perceived effectiveness reputations than decentralized INGOs do. This perceptual tension may inform INGO governance reforms and future research on organizational structure, effectiveness, and leadership.